The Bilateral Contract - Castañeda, Jorge Eugenio (1969)
This paper provides an overview of the synallagmatic contract or bilateral contract in comparative law, with special focus on German and Italian law and its comparison with the Peruvian legal system. In this context, the article addresses the conceptualization, application and regulation of the bilateral contract, defining it as one that contains a plurality or reciprocity of obligations to be performed by each of the two parties. Thus, the author raises relevant issues such as the treatment of rescission or termination in this type of contract, the theory of risk and its shortcomings in the Peruvian civil code.